A Comparison of Secretaries’Job Performance at Public and Private Companies in Malang. - susi lowati (Jurnal VOK@SINDO, 2016)
This study aims to determine how good secretaries’job performance in public and private companies is as well as find out whether there are differences in job performance between the secretaries working in public and private companies. Samples were taken from 25 secretaries: 14 secretaries from public companies and 11 secretaries from private ones. The research hypothesis is that there are differences in job performance between the secretary of the government-owned companies and private companies. The variables used in this study consist of one independent variable (job performance) and three dependent variables (effectiveness, productivity and utility). The data analysis was done using T - Test and data normality test. The findings show that job performance of secretaries working in private companies is higher (the mean is 95.73) than those working in public companies (85.36). It is then important for secretaries working in public companies to improve their job performance